Corporate performance and sustainability: Evidence from listed firms in Portugal and Spain. (December 2020) - Madaleno, Mara; Vieira, Elisabete
Abstract: We examine the impact of various factors on the quality of environmental disclosure using a sample of listed companies in Portugal and Spain for the period 2010–2017 using the generalized method of moments (GMM) and adding a sustainability index created through principal component analysis (PCA). The econometric model has been used to show the practical implications of gender corporate governance (CG) indicators and the proposed index over the market and accounting-based performance measures. The study focuses on factors related to the strategy and vision of the firm, diversity within boards, and environmental factors. Results highlight that the presence of women on board increases both financial performance and sustainability practices, highly visible through market-based measures. Sustainability initiatives also increase financial performance which works also in the other way around. Still, sustainability practices by companies are highly dependent on their financial situation casting doubts on the effectiveness of the regulations obliging to insert certain types of measures within the company. Results are useful for regulatory parties, companies, and stakeholders. Companies should still be aware of the pressure posed by both shareholders and stakeholders regarding sustainability practices, and the increased gender diversity may have an intermediate role between CG, sustainability, and financial performance.